Description of Resilience in Patients Undergoing Hemodialysis - Cucu Rokayah; Dila Novita; Rizky Muliani; Sumbara Sumbara (Indonesian Journal of Global Health Research, 2022)
Patients undergoing hemodialysis result in physical and psychological problems. Psychological problems can cause a decrease in the resilience of hemodialysis patients, resulting in delays in the healing process. The purpose of this study was to determine the picture of resilience in patients undergoing hemodialysis at Al-Ihsan Hospital, Bandung Regency. The type of this research is quantitative research with correlational method. The research instrument used was the Connor and Davidson Resilience Scale (CD-RISC). The population of this study were 180 patients with a sample of 125 hemodialysis patients. The sampling technique used was purposive sampling with inclusion and exclusion criteria. Data analysis used univariate and bivariate analysis with Spearman rank correlation test. The results of the study obtained low resilience (51.2 %), each resilience indicator obtained tenacity (72.8%), strength (82.6%), and optimism (81.5%). Based on the results of the study, it can be said that patients undergoing hemodialysis at Al-Ihsan Hospital, Bandung Regency, are classified as low resilience. It is expected that hemodialysis nurses can motivate and provide optimal nursing care to increase the resilience of hemodialysis patients at Al-Ihsan Hospital, Bandung Regency.